Fibrosis stage is an independent predictor of outcome in primary biliary cholangitis despite biochemical treatment response. Issue 10 (17th October 2019) - Murillo Perez, Carla F.; Hirschfield, Gideon M.; Corpechot, Christophe; Floreani, Annarosa; Mayo, Marlyn J.; van der Meer, Adriaan; Ponsioen, Cyriel Y.; Lammers, Willem J.; Parés, Albert; Invernizzi, Pietro; Carbone, Marco; Maria Battezzati, Pier; et al.
Summary: Background: Fibrosis stage predicts prognosis in patients with chronic liver disease independent of aetiology, although its precise role in risk stratification in patients with primary biliary cholangitis (PBC) remains undefined. Aim: To assess the utility of baseline fibrosis stage in predicting long‐term outcomes in the context of biochemical risk stratification Methods: In a large and globally representative cohort of patients with PBC, liver biopsies performed from 1980 to 2014 were evaluated. The predictive ability of histologic fibrosis stage in addition to treatment response at 1 year (Toronto/Paris‐II criteria), as well as non‐invasive markers of fibrosis (AST/ALT ratio [AAR], AST to platelet ratio index [APRI], FIB‐4), for transplant‐free survival was assessed with Cox proportional‐hazards models. Results: There were 1828 patients with baseline liver biopsy. Advanced histologic fibrosis (stage 3/4) was an independent predictor of survival in addition to non‐invasive measures of fibrosis with the hazard ratios ranging from 1.59 to 2.73 ( P < .001). Patients with advanced histologic fibrosis stage had worse survival despite biochemical treatment response, with a 10‐year survival of 76.0%‐86.6% compared to 94.5%‐95.1% depending on the treatment response criteria used. Poor correlations were observed between non‐invasive measures of fibrosis and histologic fibrosis stage. Conclusion: Assessment of fibrosis stage grants prognostic value beyond biochemical treatment response at 1 year. This highlights the need to incorporate fibrosis stage in individual risk stratification in patients with PBC, partly to identify those that may derive benefit from novel therapies. Abstract : LINKED CONTENT This article is linked to Bowlus and Levy and Carbone et al papers. To view these articles, visit https://doi.org/10.1111/apt.15576 and https://doi.org/10.1111/apt.15583 .